2020
DOI: 10.1002/brb3.1557
|View full text |Cite
|
Sign up to set email alerts
|

Nonrapid eye movement sleep and risk for autism spectrum disorder in early development: A topographical electroencephalogram pilot study

Abstract: Objective Autism spectrum disorder (ASD) is a pervasive neurodevelopmental disorder that emerges in the beginning years of life (12–48 months). Yet, an early diagnosis of ASD is challenging as it relies on the consistent presence of behavioral symptomatology, and thus, many children are diagnosed later in development, which prevents early interventions that could benefit cognitive and social outcomes. As a result, there is growing interest in detecting early brain markers of ASD, such as in the electroencephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…Age and gender (here we examined only boys) may be further factors accounting for the variability in the sleep findings among studies. For example, in a recent study, 13- to 30-months old children with ASD showed reduced theta and fast spindle-band power compared to TD children during a nap [ 75 ]. Moreover, ASD is marked by brain overgrowth in early childhood which later abnormally slows down [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age and gender (here we examined only boys) may be further factors accounting for the variability in the sleep findings among studies. For example, in a recent study, 13- to 30-months old children with ASD showed reduced theta and fast spindle-band power compared to TD children during a nap [ 75 ]. Moreover, ASD is marked by brain overgrowth in early childhood which later abnormally slows down [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a number of EEG studies showing atypical sleep architecture in young children with ASD (e.g. Arazi et al, 2019;Farmer et al, 2018;Lehoux et al, 2019;Page et al, 2020). Particularly, atypical slow wave activity (Arazi et al 2019;Lehoux et al 2019) and reduced sleep spindle generation (Farmer et al 2018) as observed with EEG in young children with ASD has been associated with altered thalamocortical FC during deep sleep (Baran et al 2019).…”
Section: Possible Mechanisms: Atypical Modulation Of Thalamocortical mentioning
confidence: 64%
“…Page et al used a 124-or 128-channel high density EEG net to examine EEG band power during a nap with an average duration of 78 min in children 13-30 months old with ASD. They detected differences in the NREM spectral features between TD and ASD, with a significant decrease of fast theta power in the temporo-central cluster and a significant increase in beta power in the right temporo-occipital cluster (p < 0.05) [42].…”
Section: Microstructural Eeg Parametersmentioning
confidence: 97%
“…Ten studies focused on different electrophysiological features of the microstructure of sleep [27,28,31,33,35,42,43].…”
Section: Microstructural Eeg Parametersmentioning
confidence: 99%
See 1 more Smart Citation